Science Laboratory Management in Learning - Wati, Qoriah Meri Indah Kimia; Fitria, Happy; Putra, Alhadi Yan (Yayasan Sembilan Pemuda Indonesia, 2024)
The science laboratory is one of the facilities and infrastructure in schools that must be well maintained because it is the place where teachers and students carry out science learning activities through practicums. The characteristics of science learning include living and non-living objects, it is abstract, so it is very difficult for students to understand if the learning that takes place does not run optimally and efficiently. Practicum is an inseparable part of science learning subjects. Laboratories are needed as a place of learning to provide real experience to students as a supporting factor in implementing science learning. This research aims to identify and describe planning, management, management, movement, management, and supervision of science laboratories and obstacles in learning carried out by SMP Negeri 34 Palembang with descriptive research using a qualitative approach. The data in this research was obtained through observation, interviews with informants, and documentation as supporting data. This research can be concluded based on the results of the research. The management functions of laboratory management in science learning at SMP Negeri 34 are; The planning and management of the science laboratory has been carried out well, the organization of the management of the science laboratory has a laboratory organizational structure, the organizer of the management of the science laboratory has implemented the work plan well, and supervision of the science laboratory has been carried out by the school principal and supervisor through. Obstacles to implementing science laboratory management in student learning consist of Limited funds, laboratory managers who have multiple jobs, lack of management staff, lack of motivation, and lack of supervision by laboratory staff.